LEARNING ANALYTICS IN ONLINE EDUCATION: INVESTIGATINGSTUDENT ENGAGEMENT AND INTERACTION PATTERNS IN DIGITAL LEARNING ENVIRONMENTS - Rahman, Dr. Farid; Hassan, Ahmad Faizal; Omar, Siti Nur Hidayah (International Journal For Research In Educational Studies, 2025)
The student interaction and engagement patterns in the digital learning settings through learning analytics framework.Due to the rapid increase in online education, the way the student engages with digital learning platforms has become acritical issue ofenhancing teaching strategies and learning outcomes. The research examines a dataset of educationaltechnology comprising demographic data of students and the interaction records in detail obtained using an onlinelearning platform. The data cover the activities of watching the videos, submitting assignments, quizzes, participating indiscussions, downloading resources, and notes taking. Patterns of engagement, duration of interaction, frequency ofactivity and the correlation between behavioral engagementand learning performance were analyzed quantitatively. Theresults indicate that students engage in various types of interaction, note-taking and attempts at quizzes being the mostcommon. Video-based learning and assessment-related activities had longerinteraction times, which demonstrated moreprofound learning. The findings also indicate that mobile gadgets are the most utilized technology in accessing onlinelearning platforms which makes mobile friendly learning settings paramount. Moreover, the analysis reveals thatsustained engagement has a positive correlation with the better academic performance. In general, the research highlightsthe value of learning analytics in explaining the behavior of students in digital education systems and offers insights to beutilized in the development of more efficient and engaging online learning settings.